The future of impact assessment in Austria and Germany – streamlining impact assessment to save the planet?. Issue 3 (4th May 2023) - Geißler, Gesa; Jiricka-Pürrer, Alexandra
ABSTRACT: Streamlining IA for low-carbon activities respectively to reach climate mitigation targets has become a new trend. In Austria and Germany, likewise in many other countries authorities and project developers discuss acceleration of impact assessment procedures looking particularly at public participation as one of the factors suspected to lead to prolongation of procedures. Additionally, also inspired by the EU provisions regarding climate change and renewable energies, experts discuss streamlining between regional and project level, thus between SEA and EIA. In this letter the authors look critically at the most recent developments related to the ambition to accelerate particularly the planning and commissioning of wind energy infrastructure and discuss both chances but also negative consequences and limitations. These are related to several factors such as the assessment at the appropriate planning level or the quality of data. The letter provides implications for IA practice and alternative suggestions which might support efficient impact assessment while maintaining or improving its quality particularly having in mind the various conflicting targets related to, i.e., biodiversity, human health and climate change mitigation.